Kala azar in Nepal: Estimating the effects of socioeconomic factors on disease incidence - Adhikari, SR; Supakankunti, S; Khan, MM (Kathmandu University Medical Journal, 2010)
<!--[if gte mso 9]> maya 11.9999 <![endif]--><!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Background: The incidence of Kala Azar (KA), a neglected tropical infectious disease, describes the pattern of disease, but is not principally concerned with explaining its causes. The transmission of the infectious diseases is determined by the complex interactions between environmental and socioeconomic factors. Environmental factors are predicted to have a significant impact on disease transmission; moreover, socioeconomic factors modify the magnitude and direction of these impacts. A number of studies have examined possible determinants of KA in endemic countries of the world; however, most of them appear to have used either qualitative approaches or subjective speculations. None of the studies indicates in quantitative terms the potential effects of poverty-alleviation programs on the incidence of KA. Materials and methods: Data related to charecteristics of community were collected from primary as well as secondary sources. Underlying socioeconomic determints on KA incidence were estimated by exploiting a linear multiple regression. Results: The multivariate analysis has confirmed that burden of KA is disproportionately borne by vulnerable and marginalized groups. KA is most entrenched in the poorest communities. Elimination of KA is directly related to poverty alleviation because if the poverty incidence reduces by10 percent, it will lead to reduction of KA incidence by 16 percent. The strategy for disease control or elimination should shift from traditional disease-centered approaches to a holistic approach that can break the links between poverty and KA. Conclusions: To achieve the target of elimination of KA in Nepal by 2015, the poverty incidence should be reduced from existing poverty 27 percent to at least 16 percent in KA endemic areas. The association between poverty and KA reflects causality running in both directions: poverty multiplies KA incidence and KA pushes poor into marginal poor or further poverty. Key words: Kala azar; Socioeconomic factors; Leishmaniasis DOI: 10.3126/kumj.v8i1.3225 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 73-79